CTNI-62. LONG-TERM EFFICACY AND SAFETY OF LAROTRECTINIB IN PATIENTS WITH TROPOMYOSIN RECEPTOR KINASE (TRK) FUSION PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (14th November 2022) - Perreault, Sébastien; Drilon, Alexander; Lassen, Ulrik N; Geoerger, Birgit; Nysom, Karsten; Øra, Ingrid; Gavrilovic, Igor T; Norenberg, Ricarda; Bernard-Gauthier, Vadim; De La Cuesta, Esther; Laetsch, Theodore W; Doz, François; et al.
Abstract: BACKGROUND: Larotrectinib is a highly selective TRK inhibitor that demonstrated an objective response rate (ORR) of 30% and a 24-week disease control rate (DCR) of 73% across 33 evaluable adult and pediatric patients with TRK fusion primary CNS tumors, as of July 2020 (Doz et al, Neuro Oncol 2021). We report updated data on an expanded dataset. METHODS: Patients with TRK fusion primary CNS tumors in two clinical trials (NCT02637687, NCT02576431) were included. Responses were investigator-assessed. RESULTS: As of July 2021, 38 patients with TRK fusion primary CNS tumors (median age, 10.8 [range 1.3–79.0] years) were identified: high-grade glioma (HGG; n = 23), low-grade glioma (LGG; n = 9), and other (n = 6). Sixteen (42%) patients had ≥ 2 prior systemic therapies. ORR for 37 evaluable patients was 30% (95% confidence interval [CI] 16–47): three complete responses, eight partial responses, 21 stable disease (16 patients ≥ 24 weeks), and five progressive disease. For pediatric patients (n = 28), the ORR was 39% (95% CI 22–59). For pediatric patients with HGG and LGG, ORRs were 43% (95% CI 18–71) and 38% (95% CI 9–76), respectively. ORRs for patients with 0, 1, 2, and ≥ 3 prior therapies were 33%, 20%, 38%, and 38%, respectively. Median time to response was 1.9 months. The 24-week DCR was 73% (95% CI 56–86). Median duration of response (DoR) was not reached; 12-month DoR rate was 64%. Median progression-free survival was 16.5 months (95% CI 6.7–not estimable). Median overall survival (OS) was not reached; 24-month OS rate was 65%. Treatment duration ranged from 0.1+ to 38.7+ months. Treatment-related adverse events (TRAEs) were mostly Grade 1–2. No patients discontinued treatment due to TRAEs. CONCLUSION: Larotrectinib demonstrated a high DCR, rapid and durable responses, and a manageable safety profile in patients with TRK fusion primary CNS tumors.